Impact of oral microbiota on pathophysiology of GVHD - Yamamoto, Akira; Kambara, Yui; Fujiwara, Hideaki (Frontiers in Immunology, 2023)
Allogeneic transplantation of hematopoietic cells is the only curative therapy for several hematopoietic disease in which patients receive cytotoxic conditioning regimens followed by infusion of hematopoietic stem cells. Although the outcomes have improved over the past decades, graft-versus-host-disease (GVHD), the most common life-threatening complication, remains a major cause of non-relapse morbidity and mortality. Pathophysiology of acute GVHD characterized by host antigen-presenting cells after tissue damage and donor T-cells is well studied, and additionally the importance of recipient microbiota in the intestine is elucidated in the GVHD setting. Oral microbiota is the second most abundant bacterial flora in the body after the intestinal tract, and it is related to chronic inflammation and carcinogenesis. Recently, composition of the oral microbiome in GVHD related to transplantation has been characterized and several common patterns, dysbiosis and enrichment of the specific bacterial groups, have been reported. This review focuses on the role of the oral microbiota in the context of GVHD.